Scholar-Practitioner Exploration of EL Access and Definitions: Going to the heart of ELTHE's special issues defining experiential education. - Heinrich, Bill; Meyer, Josh; Iruoje, Tiana Williams (Experiential Learning and Teaching in Higher Education, 2024)
There has been a longstanding societal push to diversify the student body of colleges and universities by improving access. Increasing access through the diversification of their membership bases is also an expressed goal of the experiential learning professional societies (SEE and AEE). Overlaying this charge with SEE’s initiative to revisit the defining features of experiential learning (EL) creates an opportunity to consider how definition impacts access to the field. To address this challenge, we employed a scholar-practitioner research methodology exploring the question, How does the definition of experiential learning impact access? This process involved each author addressing three related questions individually before we compared responses and analyzed our data. We found differences in perspective (e.g., administrative, educational, and student) and differences in needs (immediate need for funding to pay for additional EL-related expenses and need for data to show that EL works). Clarifying these differences may help bridge discrepancies in espoused theory and theory in use, thereby increasing opportunities to access EL through definition.